2017
DOI: 10.1080/24750573.2017.1309817
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine may reduce repetitive behaviors in children with autism: a case series

Abstract: Objective: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impairment in social communication and interaction, and restricted, stereotypic, repetitive behaviors. Behavioral problems are common in children with ASD. Herein, we report the effect of N-acetylcysteine (NAC) treatment on repetitive behaviors in 10 children with ASD. Methods: Ten children with ASD were assessed using the Childhood Autism Rating Scale and Aberrant Behavior Checklist (ABC). The clinical follow-up was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…Hardan, et al [20] demonstrated that the administration of NAC is responsible for significantly improving patient's irritability, also by leading to a decrease in stereotyped behaviors. That is also pointed by Çelebi Fahri, [21], in a case report with eight patients. It is believed that two possible mechanisms may be related to those results: antioxidant and glutamatergic modulation.…”
Section: Resultssupporting
confidence: 58%
“…Hardan, et al [20] demonstrated that the administration of NAC is responsible for significantly improving patient's irritability, also by leading to a decrease in stereotyped behaviors. That is also pointed by Çelebi Fahri, [21], in a case report with eight patients. It is believed that two possible mechanisms may be related to those results: antioxidant and glutamatergic modulation.…”
Section: Resultssupporting
confidence: 58%
“…In particular, a study showed that the drug was well tolerated by the patients and could significantly reduce irritability [93]. Furthermore, other studies reported that stereotypical behaviors could be improved after 8 weeks of treatment with NAC [94,95]. Another antioxidant tested in the context of ASD is vitamin C. When this molecule was supplemented to ASD children for 30 weeks, a significant improvement in sensorimotor behaviors could be observed [96,97].…”
Section: Targeting Ros To Treat Asdmentioning
confidence: 99%
“…Furthermore, other studies reported that the stereotypical behaviors could be improved after 8 weeks of treatment with NAC [94]. Vitamin C is another antioxidant that could treat ASD.…”
Section: Discussionmentioning
confidence: 99%